Analisis Kelayakan Usaha Penangkaran Benih Padi di Desa Gunung Mulia, Kecamatan Babulu, Kabupaten Penajam Paser Utara - Irvan Ardiansyah; Rita Mariati (Universitas Khairun, 2023)
Seed breeding is an effort to produce superior seeds as source seeds which will later be used for planting. This research was conducted with the aim of finding out the feasibility of the rice seed breeding business in Gunung Mulia Village. This research was carried out in Gunung Mulia Village from June 2023 to August 2023 with a sample size of 8 people. The research was carried out by calculating production costs, revenues and business income so that later the Revenue Cost Ratio value could be obtained. Production costs are divided into two, namely fixed costs and variable costs. The results of the research show that the average production cost in the rice seed breeding business in Gunung Mulia Village is Rp. 12,283,625 mt-1 consisting of fixed costs of Rp. 1,778,313 mt-1 and variable costs Rp. 10,505,313 mt-1, average revenue Rp. 27,045,000 mt-1 resulting in income of Rp. 14,761,375 mt-1 and an average R/C value of 2.18. R/C value for the rice seed breeding business in Gunung Mulia Village is 2,18 which means that for every rupiah of production costs spent, revenue will be 2,18 which means the rice seed breeding business is feasible to do and develop.Keywords: breeding of rice seeds, feasibility analysis, income